Study on the Earth-Covered Magazine Models under the Internal Explosion - Cheng Gong; Yan-Yu Qiu; Zhi-Lin Long; Lu Liu; Guan-Gan Xu; Ling-Ming Yang (Shock and Vibration)
The use of earth-covered magazines (ECMs) is increasingly prevalent in protective engineering due to their concealment and cost-effectiveness. To explore the optimal thickness of earth covering for ECMs, scaled model tests were conducted under explosive charges equivalent to 30 kilograms of TNT. The resulting overpressure outside the model in the 180° direction was measured. Subsequently, computational analyses were conducted employing LS-DYNA software to examine these experimental findings. The findings indicate that increasing the thickness of the rear soil can mitigate peak overpressure, delay the air shock wave’s arrival time, and reduce the impulse of the positive phase. The numerical calculations closely align with experimental data, with peak overpressure deviation remaining under 10%. The shock wave initially impacts the top of the model before reaching the rear, with soil scattering more pronounced in the 90° direction compared to the 180° direction. Furthermore, an analysis of soil energy absorption rate variation was conducted based on energy conservation principles. These results provide valuable insights for optimizing the design and construction of ECMs.